(untitled) (Research, Society and Development, 2022)
ASD is a disorder with many peculiarities that have not yet been discovered by science, for this reason, developing any experience with an autistic person requires empathy, humanity and patience. In a dental clinic, professionals will face a series of challenges during treatment with an autistic child. Studies show that in order to obtain an efficient and excellent dental treatment, it is necessary to use specific methods together with the support of the family, making a dignified and effective service. This article aims to present, through a literature review, conducts to be addressed in the dental care provided to children with autistic spectrum disorder, aiming at a better treatment for these patients. The database used in the research was through PubMed and Latin American and Caribbean Literature on Science and Health (LILACS) and the theoretical basis consisted of scientific articles, books, monographs and journals.